Low glucose at 3-hour 100 gram oral glucose tolerance test: implications for glucose control. (12th December 2022) - Reicher, Lee; Lavie, Anat; Attali, Emmanuel; Fouks, Yuval; Feinmesser, Larissa; Landesberg, Isca; Yogev, Yariv; Maslovitz, Sharon
Abstract: Objective: To assess the clinical significance of a low 180-minute glucose value in a 100 g oral glucose tolerance test (OGTT) and a single high abnormal value. Methods: A retrospective cohort study. The study group included women with 180-minute plasma glucose levels of ≤60 mg/dL and one abnormal value in the OGTT. The control group was comprised of women with one abnormal value in the OGTT and normal 180-minute glucose value. The primary outcome was glycemic control, defined as fasting blood glucose measurements > 90 mg/dL or post-prandial glucose values >140 mg/dL or 120 mg/dL (one-hour and two-hour post-prandial, respectively) in >30% of the measurements. Secondary outcomes were the rate of insulin treatment and the perinatal outcome consisting of birthweight, large-for-gestational-age, and polyhydramnios. Results: Three hundred and one women were included, 143 in the study group and 158 in the control group. Pre-pregnancy BMI, first trimester fasting glucose levels, previous GDM, and familial diabetes were similar for both groups. Suboptimal glycemic control was more prevalent among the women in the study group (14% vs. 5.1%, respectively, p = .01). The need for insulin treatment was similar in both groups. Conclusions: Women with one abnormal value and a 180-minute hypoglycemia in the OGTT are at increased risk for suboptimal glycemic control.